The fall and rise of gonorrhoea incidence in Israel: an international phenomenon?. Issue 2 (1st April 2003) - Green, M S; Anis, E; Gandacu, D; Grotto, I
Abstract : Background: There is evidence of a recent resurgence of the incidence of gonorrhoea in some countries. Aim: To examine trends in gonorrhoea incidence in Israel and compare them with the United States and countries in Europe Method: The 1967–2001 annual incidence of gonorrhoea in Israel was obtained from the Israel Ministry of Health's department of epidemiology and for the United States from summary reports of the Centers for Disease Control. The incidence of gonorrhoea in European countries was extracted from the World Health Organization, Health for All database. Results: In Israel, following a long period of decline from 40 per 100 000 in 1970 to 0.74 per 100 000 in 1997, incidence rates began to increase in 1998 to 13.8 per 100 000 in 2001. This pattern parallels those observed in a number of European countries and to some extent, in the United States. Most reported morbidity in Israel occurs among males aged 20–44 years. Conclusions: The resurgence of gonorrhoea does not appear to be explained solely by behavioural changes. Transmission of the disease should be further studied among different subpopulations in order to develop new prevention strategies.